Energy optimised design attributes checklist of a terrace house nexus to the Malaysian smart grid system via content analysis approach / Ahmad Haqqi Nazali Abdul Razak ... [et al.] - Abdul Razak, Ahmad Haqqi Nazali; Ahmad, Nur Azfahani; Khalil, Natasha; M.Leardini, Paola (2022)
Design plays a pivotal role in energy use for a residential unit. Alongside the nationwide smart grid system deployment, further energy optimisation strategies are possible through design enhancement of these residential units. Despite various advantages of the Smart Grid, design aspects connected to the Smart Grid system has yet to be explored. Thus, the aim of this paper is to identify the key attributes of smart grid system and design nexus intended to elucidate opportunities for further enhancements. A Smart Grid – Design Parameter (SG-DP) building checklist is developed and proposed based on content analysis approach conducted on thirteen (13) selected sustainable tools documents in Malaysia. Outcome of the building checklist proposed may provide critical insights regarding design attributes significant to the smart grid system and benefit the residential stakeholder.